Evaluation of broadband usage and service quality in Kota Kinabalu, Sabah / Ridwan Mokhtar, Yaakob Mahmood and Nasrul Fadhrullah Isa - Mokhtar, Ridwan; Mahmood, Yaakob; Isa, Nasrul Fadhrullah (2010)
This survey study was carried out to measure broadband usage and service quality in Kota Kinabalu. Data was collected using a questionnaire from a random sample of 301 respondents in nine major areas in Kota Kinabalu. The main focus of the study is to examine the profile of broadband users as well as to measure the service quality that consists of three dimensions: product, customer service and charges/billing. Respondents were asked to rate the importance and their satisfaction level on 27 items on broadband service in their area on a 5-point Likert scale. Customer Satisfaction Index (CSI) is measured by the mean scores of all items in the three dimensions. The results showed that broadband users are mostly young professionals in the private sector, with moderate to high income and high education. This indicates that the broadband market has a great potential for expansion. Based on the results, it shows that service providers have provided an above average service in their charges/billing system but several aspects of the product and customer services need to be upgraded. Comparisons of CSI using ANOVA reveal that satisfaction is below average across all demographic variables, except gender.